Desfechos perioperatórios primários da endarterectomia e angioplastia no tratamento da estenose de artéria carótida - Menegola, Vinícius Matos (2021)
Stroke has been among the most relevant chronic diseases of our time and it is the third leading cause of morbimortality in the west, which may cause cognitive and motor deficits in most patients. The vast majority of strokes in Brazil have an ischemic etiology and approximately 80% of the cases have the participation of extracranial carotid stenosis in its etiopathogenesis. Studying the primary perioperative outcomes, as well as discussing carotid revascularization techniques and their indications allow for a better approach and optimization of the treatment. Retrospective observational study in patients submitted to carotid endarterectomy (CEA) and transluminal carotid angioplasty (TCA), based on the review of 78 medical records divided into 2 groups, according to the presence or absence of symptoms. Patients selected for surgical intervention comprised both asymptomatic with stenosis greater than 80% and symptomatic with >70% stenosis of the lumen of the internal carotid artery (ICA), basing the degrees of stenosis on the NASCET/ECST criteria. CEA was performed in 75 patients and only 3 patients carried out PTA. Critical ICA stenosis was found in 100% of the studied patients; from those, 49 (62.8%) were male. Of the 78 patients who underwent procedures, 46 (58.97%) were symptomatic and 32 (41%) asymptomatic. Among the perioperative clinical outcomes, 4 (5.12%) cases of cerebrovascular accident (CVA) were identified, with 3 (6.52%) patients in the group of symptomatic patients and only 1 (3.125%) case among the asymptomatic ones. No cases of acute myocardial infarction (AMI) were observed, and no deaths from any cause were found in the perioperative period. The low rates of perioperative clinical outcomes are in line with international studies and corroborate the safety of the procedure in this institution.